Design and validation of the reflection skills self-assessment questionnaire (RSSAQ) - Hadi Hamedfar; Mohammad Barzegar; Fatemeh Ranjbar; Saeideh Ghaffarifar (Journal of Education and Health Promotion)
BACKGROUND: Reflection is one of the main components of the medical sciences curriculum. It is one of the learner-centered educational strategies, leading to deep learning, and is necessary to attain professional capabilities. A pertinent challenge is how to assess reflection. This study was conducted to design and assess psychometric characteristics of medical sciences students’ reflection skills self-assessment questionnaire (RSSAQ) in Persian. MATERIALS AND METHODS: This is a methodological explorative study conducted at our University of Medical Sciences. First, an item pool was collected from both the literature review (previously designed questionnaires and existent models of reflection) and experts’ and researchers’ perspectives. Then the initial version of the questionnaire was presented to 19 experts and 50 students to assess the face and content validity. To assess the reliability, 48 students filled out the questionnaire twice at a one-week interval. To assess the construct validity, exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were done. For doing so, 151 students filled out the questionnaire. The data was analyzed using IBM SPSS (Statistical Package for the Social Sciences) Statistics for Windows version 16 and Analysis of Moment Structures (AMOS). RESULTS: The content validity index (CVI), content validity ratio (CVR), and impact score (IS) for the questionnaire came out to be 0.91, 0.75, and 4.68, respectively. Regarding the reliability, Cronbach’s alpha and intraclass correlation coefficient (ICC) were, respectively, 0.75 and 0.8 (with a 95 percent confidence interval). Regarding the construct validity, three factors were extracted, labeled as “readiness to reflect” (RTR), “reflection in action” (RIA), and “reflection on action” (ROA). It became clear that this questionnaire can predict 36.8 percent of variations in reflective behavior or process in students. CFA determined that there is a positive and significant correlation between RIA and ROA factors. However, the RTR factor has a negative correlation with the other factors and vice versa. CONCLUSION: The questionnaire designed in this study for reflection self-assessment had acceptable psychometric characteristics and can be applied in curriculum planning, educational evaluations, and designing educational interventions.